1998
DOI: 10.1038/sj.cdd.4400413
|View full text |Cite
|
Sign up to set email alerts
|

UVA exposure of human skin reconstructed in vitro induces apoptosis of dermal fibroblasts: subsequent connective tissue repair and implications in photoaging

Abstract: The skin reconstructed in vitro has been previously shown to be a useful model to investigate the effects of UVB exposure (Bernerd and Asselineau, 1997). The present study describes the response to UVA irradiation. Major alterations were observed within the dermal compartment. Apoptosis of fibroblasts located in the superficial area of the dermal equivalent was observed as soon as 6 h after irradiation, leading to their disappearance after 48 h. This effect was obtained without major alterations of epidermal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 31 publications
(41 reference statements)
5
91
0
1
Order By: Relevance
“…Very importantly, overexpression of galectin-7 in sunburn keratinocytes also was observed in human skin ex vivo after UVB irradiation. The present findings put forward the role of galectin-7 in UVBinduced apoptosis of epidermal keratinocytes and further support previous studies (20,47,48) regarding the usefulness of skin reconstructed in vitro in evaluating effectors of cell fate and differentiation in epidermis.…”
Section: High Level Of Galectin-7 Expression In Sunburn͞apoptotic Kersupporting
confidence: 75%
“…Very importantly, overexpression of galectin-7 in sunburn keratinocytes also was observed in human skin ex vivo after UVB irradiation. The present findings put forward the role of galectin-7 in UVBinduced apoptosis of epidermal keratinocytes and further support previous studies (20,47,48) regarding the usefulness of skin reconstructed in vitro in evaluating effectors of cell fate and differentiation in epidermis.…”
Section: High Level Of Galectin-7 Expression In Sunburn͞apoptotic Kersupporting
confidence: 75%
“…Pourzand et al (51) reported UVAinduced apoptosis through antioxidant properties of Bcl-2 in Rat 6 fibroblasts. Studies by Bernerd et al (52) demonstrate that UVA induces apoptosis of fibroblasts in the dermis without significant effects on kertinocytes residing in the epidermis by using an in vitro reconstructed skin model. These data suggest a differential effect of UVA on sensitivity to apoptosis depending upon cell type.…”
Section: Discussionmentioning
confidence: 99%
“…These situations were repaired in skin equivalents that were maintained in culture for extended periods of time. In another study, they found that UVA exposure induces responses specific to the dermal compartment of skin equivalents (Bernerd and Asselineau, 1998). Fibroblasts in the upper regions of the 'dermal' component of the skin equivalents underwent apoptosis and disappeared from the constructs.…”
Section: Dermal and Skin Equivalents As Biological Modelsmentioning
confidence: 99%